Pemanfaatan Teknologi dan Aplikasi QGIS untuk Pemetaan Digital Potensi Desa Pancuran Gading Kabupaten Kampar Provinsi Riau - Mardiana Mardiana; Anggun Dwi Cahyani Fitri; Putri Mardiyanti; Haifa Muthi; Fuad Zikri; Gita Putri Sadelina; Al Arif Febrian; Ahmad Zakaria; Muhammad Ijlal Ghaly; Shelly Isya Ramadhani; Annisa Delia Putri (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Research carried out by KKN students in the form of community service aims to facilitate public access to location points in a place or region through public facilities in Pancuran Gading Village, Tapung District, Kampar Regency, Riau Province. This research was carried out using an implementation technique in the form of Participatory Action Research (PAR) Method (Participatory Action Research) with three principles which serve as a reference for service research. In carrying out the mapping of the coordinates of public facilities in Pancuran Gading Village, the research we carried out was coordinated by the village, namely Mr. Hari Isnaldi as Secretary of Pancuran Gading Village, Tapung District. Villages are seen as the starting point for empowering regional potential. With this village potential mapping, it can be used to find out existing potential information, and can be used as material for village development planning. This potential map was created using digital mapping technology in the form of the QGIS application which is viewed through a map and then created manually in the application. With the success of the students, they created a map as a means used by the community to access public facilities or places in Pancuran Gading Village.